Gameplays Versus Playstyles: The Social Construction of Transmediated Communities Among Filipino Children Gamers in Minecraft and Roblox - Sayuno, Cheeno Marlo (UI Scholars Hub, 2021)
The children of today’s generation are considered as digital natives, which means that they have the capacity to navigate technological terrains to the best of their abilities and create online communities in new storyworlds. Minecraft and Roblox, two sandbox open-world mobile games, are manifestations of such ability to create worlds, survive in difficult gaming situations, face opponents in combat, and interact with players within a community. Even more so, such transmedia engagements allow the child participants, as evidenced in this study, to transact with players and the app itself to introduce new playstyle strategies that complement or subvert the gameplays originally set by developers. This study aims to explore how child users navigate through various transmedia storyworlds to socially construct shared meanings of their engagements. By proposing a novel “techno-immersion” as a method of data construction, the researcher joined four child participant–characters in their journey as they traverse from one gaming storyworld to another. Several transactions emerge in such a transmedia engagement, including player-to-player negotiation of playstyle; diverging playstyle away from prescribed gameplay; harnessing the gameplay rules to achieve personal goals in engagement; player-to-player and player-to-media negotiations to create new gameplay; and interaction as means of negotiation. It was also found that child users of mobile games are empowered in harnessing the rules of the game to their personal gaming goals and freeing from the binds that limit them from their engagements, towards becoming fully realized child characters in their transmedia storyworlds.